THE IMPLEMENTATION OF LADDER DRILL TRAINING TO IMPROVE DRIBBLING SKILLS IN FUTSAL EXTRACURRICULAR ACTIVITIES - Muhammad Suhdy (Teaching and General Education Studies, 2026)
Dribbling is one of the fundamental skills in futsal that requires agility, coordination, and effective ball control. This study aimed to examine the effect of ladder drill training on improving dribbling skills among students participating in futsal extracurricular activities. This study employed an experimental method using a one-group pretest–posttest design. The participants were 20 male students involved in futsal extracurricular activities at MAN 2 Lubuklinggau City. The ladder drill training program was conducted over 12 sessions with movement variations designed to enhance agility, foot coordination, and ball control. Data were collected using a zig-zag dribbling test measured by completion time. The findings indicated a significant decrease in the average dribbling time from 14.27 seconds in the pretest to 12.91 seconds in the posttest, representing an improvement of 1.36 seconds (9.50%). Statistical analysis using a paired-sample t-test revealed a calculated t-value of 18.85, which exceeded the critical t-value of 1.729 at a significance level of α = 0.05. Ladder drill training has a significant positive effect on improving dribbling skills in futsal players. This training method can be effectively integrated into regular futsal training programs to enhance technical performance.